Formulation And Evaluation Of Gastroretentive Indapamide Micro Balloons In Combination With Telmisartan Minitablets - NEHA M.MUNOT; AMRITA N.BAJAJ (International Journal of Pharma and Bio Sciences, 2011)
The objective of present study was to develop and evaluate dosage form containing floating micro balloons of indapamide, in combination with immediate release minitablet of telmisartan, for treatment of hypertension. Microballoons of indapamide were prepared using Emulsion solvent diffusion technique. These were evaluated for entrapment efficiency, particle size, particle shape using scanning electron microscopy technique, percentage buoyancy and invitro release. The formulations were optimized using 23 factorial design. Telmisartan minitablets were prepared using direct compression method and were evaluated for parameters like weight variation, hardness, friability, disintegration time and invitro release. Micoballoons and minitablets were filled in a hard gelatin capsule. Capsules were evaluated for invitro drug release studies using High performance liquid chromatography technique. Telmisartan was released immediately within 20 minutes while indapamide was released over 24 hours following Higuchi model. Synergistic effect was confirmed by animal studies. Blood Pressure in animal models was measured using Tail Cuff Method.